FANATISME MADZHAB DALAM TAFSIR AL AL-KASYAF - iklima, Ima (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2024)
The Qur'an has a general nature and requires deeper explanations. The flexibility in interpreting the Qur'an results in an ever-changing interpretation process over time and place. Schools of thought and scholarly affiliations also influence the approach of interpreters in interpreting the Qur'an. One famous tafsir is Al-Kasysyaf by Az-Zamakhsyari, known for its beautiful use of vocabulary and its connection to the Mu'tazilah. The Mu'tazilah emphasize the concepts of monotheism, justice, promises, and threats in their interpretations. Based on its methodology, this study is a literature review (library research) since the data sources are primarily books and literature related to the research topic, including the works of al-Zamakhshary and other relevant sources. This paper discusses the fanaticism of Zamakhsari in interpreting his tafsir, particularly in the interpretation of the attributes of Allah. Zamakhsari adopts the views of the Mu'tazilah, who deny the mortality of Allah and interpret words such as "hand" and "eye" with different meanings. Additionally, the Mu'tazilah reject many of Allah's attributes that imply similarity to created beings. They reinterpret the descriptions of Allah, such as the interpretation of Allah's presence above the 'arsh (throne). The Mu'tazilah also deny the possibility of seeing Allah with the naked eye on the Day of Judgment, using Quranic verses that state that Allah cannot be reached by human sight, yet He can see all that is visible. This research highlights the differences in the interpretation of the Qur'an, particularly regarding the attributes of Allah, between the views of Zamakhsari and the Mu'tazilah, in contrast to the beliefs of the Ahl al-Sunnah